Thermodynamic study of the influence of NADPH on the binding of methotrexate and its metabolites to a mammalian dihydrofolate reductase - Gilli, Robert M.; Sari, Jean C.; Sica, Lucas M.; Briand, Claudette M. (Biochimica et biophysica acta, 1988)
Interaction of methotrexate and some of its metabolites with a mammalian dihydrofolate reductase was studied using two complementary methods, potentiometry and microcalorimetry. The major plasma metabolite of this anticancer agent, 7-hydroxymethotrexate, was found to have a different binding behavior from that of polyglutamyl derivatives and of methotrexate itself. Indeed, 7-hydroxymethotrexate binds without a p K shift to dihydrofolate reductase, whereas polyglutamyl derivatives bind to the enzyme with a proton uptake, as the parent drug does. NADPH increases the association constant of the 7-hydroxy metabolite by a factor of 10–20, while for methotrexate and for polyglutamates this increase is about 100-fold. It was demonstrated that the enhancement of the binding by NADPH had an enthalpic origin. Finally, the binding behavior of dihydrofolate reductase seemed to be independent to its enzymatic activity.